2021
DOI: 10.3390/ijms22105245
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Activation Drives a Differentiation Program in an Oligodendroglial Precursor Model through the Modulation of Specific Biological Networks

Abstract: Protein kinase C (PKC) activation induces cellular reprogramming and differentiation in various cell models. Although many effectors of PKC physiological actions have been elucidated, the molecular mechanisms regulating oligodendrocyte differentiation after PKC activation are still unclear. Here, we applied a liquid chromatography–mass spectrometry (LC–MS/MS) approach to provide a comprehensive analysis of the proteome expression changes in the MO3.13 oligodendroglial cell line after PKC activation. Our findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 72 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…By RT-PCR analysis, we observed that the treatment with 25 μM DMF for 24 h induced a significant reduction in the Cx-32 expression compared with the control ( Figure 4 g). A recent study supported the involvement of protein kinase Cα (PKCα) in glial cell maturation and myelination [ 45 ]. The activation of PKCα has been found to drive a gliogenesis program associated with the modulation of several biological processes, including remodeling of the cytoskeleton, which is critical in the formation of differentiation processes [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…By RT-PCR analysis, we observed that the treatment with 25 μM DMF for 24 h induced a significant reduction in the Cx-32 expression compared with the control ( Figure 4 g). A recent study supported the involvement of protein kinase Cα (PKCα) in glial cell maturation and myelination [ 45 ]. The activation of PKCα has been found to drive a gliogenesis program associated with the modulation of several biological processes, including remodeling of the cytoskeleton, which is critical in the formation of differentiation processes [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 97%
“…A recent study supported the involvement of protein kinase Cα (PKCα) in glial cell maturation and myelination [ 45 ]. The activation of PKCα has been found to drive a gliogenesis program associated with the modulation of several biological processes, including remodeling of the cytoskeleton, which is critical in the formation of differentiation processes [ 45 , 46 , 47 ]. Western blot analysis showed that 24 h of treatment with 25 μM DMF induced a significant increase in PKCα expression compared with the control (DMSO) ( Figure 4 h), supporting the hypothesis of a pro-differentiative effect of DMF in Oli neu cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that various PKC isoforms drive a glycogenesis program mediating cytoskeletal remodeling, cell cycle control and metabolism modifications [35,36]. APE treatment leads to cytoskeletal modifications, with changes in cell morphology and redistribution of adhesion molecules [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PKC-α sits at the crossroads of many signal transduction pathways and is implicated in a wide range of cellular responses. Various PKC isoforms drive a glycogenesis program associated with cytoskeletal remodeling, cell cycle control and metabolism modifications [35,36]. As shown in Figure 3A, APE treatment caused a significant increase in PKCα kinase protein levels compared to the untreated cells.…”
Section: M2 Receptor Activation Induces Morphological Change In Scsmentioning
confidence: 97%